2021
DOI: 10.3390/pharmaceutics14010075
|View full text |Cite
|
Sign up to set email alerts
|

New, Biocompatible, Chitosan-Gelled Microemulsions Based on Essential Oils and Sucrose Esters as Nanocarriers for Topical Delivery of Fluconazole

Abstract: Biocompatible gel microemulsions containing natural origin excipients are promising nanocarrier systems for the safe and effective topical application of hydrophobic drugs, including antifungals. Recently, to improve fluconazole skin permeation, tolerability and therapeutic efficacy, we developed topical biocompatible microemulsions based on cinnamon, oregano or clove essential oil (CIN, ORG or CLV) as the oil phase and sucrose laurate (D1216) or sucrose palmitate (D1616) as surfactants, excipients also posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…It also allows the experimental factors to be screened beyond their factorial limits to improve the understanding of their effects on dependent variables. 35 In this study, a total of 20 experiments were generated and their responses are summarized in Table 5 . The results showed that the variations in PS, PDI, and ZP were all best explained by a quadratic model, and the quadratic models for PS, PDI, and ZP were all statistically significant ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also allows the experimental factors to be screened beyond their factorial limits to improve the understanding of their effects on dependent variables. 35 In this study, a total of 20 experiments were generated and their responses are summarized in Table 5 . The results showed that the variations in PS, PDI, and ZP were all best explained by a quadratic model, and the quadratic models for PS, PDI, and ZP were all statistically significant ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the excipient screening results, the IMQ-NLCs were prepared using STA, OA, polysorbate 80, and stearoyl polyoxyl-32 glycerides based on a hot melt homogenization followed by an ultrasonication method. 35 The BM of lipids consisting of STA and OA was melted at 75 °C followed by the addition of IMQ (3.5% of the BM, w/w) under continuous stirring. Polysorbate 80 and stearoyl polyoxyl-32 glycerides at a 50:50 ratio were dispersed in water and heated separately to 75 °C and added to the BM phase under continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, although the water contents of M1 and M2 were similar, M2 exhibited a higher viscosity compared with M1 ( p < 0.05), which can be attributed to its higher surfactant-to-co-surfactant ratio (S mix 2:1 v / v for M1 and S mix 3:1 v / v for M2) [ 36 ]. The obtained values of viscosity could impact the drug release behavior, since it has been reported that formulations characterized by low viscosity allow for an easy drug diffusion through the vehicle [ 37 ]. Although an increase in viscosity is often desired for liquid microemulsions intended for skin application, a low viscosity could have some beneficial characteristics, such as an easier administration via spray systems.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, M3, bearing the lowest viscosity, provided the release of a greater cumulative amount of the drug after 24 h with respect to M1 and M2 ( p < 0.05). As a matter of fact, it is known that a lower viscosity of a formulation allows for an easier drug diffusion through the vehicle than a higher viscosity and, consequently, a greater drug release [ 37 ]. Additionally, despite showing a greater viscosity than M1, after 24 h, M2 provided the release of a greater amount of AZT ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Some polysaccharides with natural pharmacological activity are combined with NE to load drugs. The antifungal properties of CS were combined with the antifungal drug Fluconazole (FZ), essential oils, and sucrose fatty acid esters to prepare gel microemulsions for the treatment of mycoses [ 131 ]. CS emulsions loaded with 5-fluorouracil (5-FU) are considered a promising method for delivering 5-FU.…”
Section: Polysaccharide-based Penetrationmentioning
confidence: 99%